Composição química e mineral do conteúdo ruminal de caprinos criados extensivamente no município de Mossoró/RN - Gameleira, Jucélio da Silva (2017)
Irregular distribution and the short rainy season provoke quantitative and qualitative changes in the forage support of the caatinga, contributing to the incidence of deficiencies and metabolic diseases, necessitating a study of the effect of seasonality on the chemical and mineral composition of the ruminal content of extensively raised goats In the semi-arid region of Rio Grande do Norte. A total of 40 male goats, 6 months old, with no defined racial pattern, castrated weighing approximately 20 kg were divided into two groups: mineralized (M) and without mineralization (SM) and kept in property in the municipality of Mossoró-RN, Where they grazed during the day in a caatinga area and were collected at night in sheepfold. The ruminal content was collected in four different periods: January (end of dry period), April (middle of rainy season), July (beginning of dry season) and October (dry season mid) for chemical composition evaluation (Ca, Mg, P, Na, K, Cu, Zn, N, Co, and Mn). The values of the chemical composition were all normal, with emphasis on protein that was above 10% in all periods. The minerals presented in varied amounts between the periods, with smaller values in the period Mc without influence of the mineralization for all the periods. The ruminal content presented satisfactory chemical and mineral composition in all evaluated periods, meeting the nutritional requirements, suggesting the nutritional quality of the native vegetation of the caatinga